Pengaruh Metode Demonstrasi Terhadap Hasil Belajar Siswa Kelas V Pada Pembelajaran IPA Materi Sifat-Sifat Cahaya di SDN 16 Bongomeme Kabupaten Gorontalo - Meylan Saleh (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
The problem in this study is whether there is an influence on the results of the use of methods demonstration of learning science material properties of the light in the Class V Student of SDN 16 Bongomeme Gorontalo. As for the purpose of this research was to determine the effect of the use of methods of demonstration against the results of science learning material properties of light Class V Student of SDN 16 Bongomeme Gorontalo. In this study, the type of research Quantitative research methods research design Experiments with Quasi Experimental Design with Control Group Design Nonequifalent form, which means that in this study there are two groups : the experimental group and the control group. Both groups were given different involves the learning. The experimental group using the method of demonstration and the control group using conventional methods. In this study, researchers will look at the effect of the use of method demonstration against the use of student learning outcomes and demonstration methods that use conventional methods to see the value of learning the results of the two groups. Data were obtained from the test instrument Posttest. From the analysis of the data obtained reject the hypothesis Ho and Ha received since the average value of the experimental group using the method of demonstration is greater than the control group using conventional methods. So use demonstration method in learning activities affect the results of science learning material properties of light Class V Student o f SDN 16 Bongomeme Gorontalo Lessons second semester 2013/2014.